Vacância residencial na Regiâo Metropolitana de Belo Horizonte: mobilização do estoque vago para a promoção de habitação de interesse social - Ana Paula Maciel Peixoto (2011)
Data on housing shortage and vacancy of homes in the Metropolitan Region of Belo Horizonte (RMBH) show that while there is a lack of properties for social housing, homes remain empty within the urban perimeter. This thesis presents a critical analysis of residential vacancy in the RMBH which aims to support the characterization of vacantstock and its possible mobilization for social housing. In addition, such research is crucial both to curb the steady increase in vacant housing in the region, and to understand the obstacles for making vacant homes available to families in need of housing. Firstly, theoretical issues concerning this phenomenon are scrutinized. Among other things, it is proposed the analysis of the relationship between real estate vacancyand capitalist housing production, aiming to clarify the scenario that causes the mismatch between housing shortage and residential vacancy. Subsequently, some reasons for the existence of vacant homes standing out in the context of RMBH are discussed, such as obsolescence and overproduction. Then, national and internationalinitiatives that include opportunities for the mobilization of the vacant stock are analyzed and, finally, presented the public policy to reduce housing vacancy in the RMBH, proposed by HVQ team for the Metropolitan Master Plan of the RMBH (PDDI-RMBH), finalized in December 2010.